Safety and efficacy of BI 695501 versus adalimumab reference product in patients with advanced Crohn's disease (VOLTAIRE-CD): a multicentre, randomised, double-blind, phase 3 trial. (October 2021) - Hanauer, Stephen; Liedert, Bernd; Balser, Sigrid; Brockstedt, Ekkehard; Moschetti, Viktoria; Schreiber, Stefan
Summary: Background: BI 695501 is a biosimilar that has demonstrated similar efficacy, safety, and immunogenicity to adalimumab reference product in patients with rheumatoid arthritis and chronic plaque psoriasis. The VOLTAIRE-CD study aimed to compare the efficacy and safety of BI 695501 with adalimumab reference product in patients with Crohn's disease. Methods: This phase 3, randomised, double-blind study was done at 92 centres in 12 countries across Europe and the USA in patients aged 18–80 years with moderately to severely active Crohn's disease (Crohn's Disease Activity Index [CDAI] score 220–450). Patients were randomly assigned 1:1 using an interactive response technology system to the BI 695501 group or adalimumab reference product group, stratified by previous exposure to infliximab (yes vs no) and simple endoscopic score for Crohn's disease at screening (<16 vs ≥16). All investigators involved in trial assessments or procedures and all patients were masked to treatment allocation until week 24. Patients received BI 695501 (40 mg/0·8 mL formulation) or adalimumab reference product (either 40 mg/0·4 mL citrate-free or 40 mg/0·8 mL) 160 mg on day 1 and 80 mg on day 15, followed by 40 mg every 2 weeks, via subcutaneous injection. The primary endpoint was the proportion of patients with clinical response (CDAI decrease ≥70 points) at week 4, with an exploratory non-inferiority margin of 0·76 for the lower limit of the two-sided 90% CI of the risk ratio (RR). The primary analysis was done in a modified full analysis set of all patients who received at least one dose of study medication and had a baseline and at least one post-baseline CDAI assessment. Safety was assessed in all patients who received at least one dose of study medication. After week 4, responders were treated until week 46; those randomly assigned to adalimumab reference product switched to BI 695501 at week 24. This study is registered at ClinicalTrials.gov (NCT02871635 ) and EudraCT (2016-000612-14). Findings: Between Jan 4, 2017, and April 5, 2018, 147 patients were enrolled and randomly assigned to BI 695501 (n=72) or adalimumab reference product (n=75). At week 4, 61 (90%) of 68 patients in the BI 695501 group and 68 (94%) of 72 in the adalimumab reference product group had a clinical response (adjusted RR 0·945 [90% CI 0·870–1·028]). In the safety analysis set, 45 (63%) of 72 patients in the BI 695501 group and 42 (56%) of 75 in the adalimumab reference product group had an adverse event during weeks 0–24; 31 (43%) and 34 (45%) had adverse events during weeks 24–56. The most common drug-related treatment-emergent adverse events during weeks 0–24 were weight increase (three [4%] patients in the BI 695501 group) and injection-site erythema and upper respiratory tract infection (three [4%] patients for each event) in the adalimumab reference product group. The only drug-related TEAEs reported in two or more patients during weeks 24–56 were weight increase and increased γ-glutamyltransferase, which occured in two (3%) patients each in the BI 695501 group. No drug-related TEAEs were reported in two or more patients during weeks 24–56 in the adalimumab reference product followed by BI 699501 group. Serious adverse events occurred in six (8%) patients in the BI 695501 group and eight (11%) in the adalimumab reference group between weeks 0–24, and two (3%) and nine (12%) patients between weeks 24–56. Adverse events of special interest occurred in two (3%) patients in each treatment group during weeks 0–24 (acute sinusitis and pulmonary tuberculosis in the BI 695501 group and anal abscess and postoperative wound infection in the adalimumab reference product group) and two (3%) patients in each group during weeks 24–56 (psoas abscess and hypersensitivity in the BI 695501 group and pulmonary tuberculosis and erythematous rash in the adalimumab reference product followed by BI 699501 group). Interpretation: Safety and efficacy were similar in patients with Crohn's disease treated with BI 695501 or adalimumab reference product. Treatment benefits were maintained in patients receiving adalimumab reference product who switched to BI 695501. These results further support the existing licensure of BI 695501 as an alternative to adalimumab reference product for patients with Crohn's disease, as well as the other indications for which BI 695501 is approved. Funding: Boehringer Ingelheim.